Practical application of post-covid business strategies: a teaching experience - Moral-Moral, María (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
A teaching innovation proposal developed in the Marketing Management subject of the Degree in Marketing and Market Research at the University of Cádiz (Spain) is presented. The initiative was evaluated through an ad hoc sequential questionnaire made up of open and closed questions. The results obtained have shown a high degree of student satisfaction with both the initiative and the overall development of the subject. It is suggested to implement teaching-learning activities connected with the environment that allow students to stimulate and develop a greater capacity for problem solving.